Team building for managers, supervisors and team leaders (Waterford, Conn. : Bureau of Business Practice, 1991)
The video is about team building and project management. It provides a straightforward discussion of what a team leader needs to consider and do to successfully complete a project. It also warns you about the possible problems that could derail a project and gives suggestion about foreseeing and avoiding these these problems
Backup available in VHS
Keywords: Work groups; Quality circles